2018
DOI: 10.1002/celc.201801146
|View full text |Cite
|
Sign up to set email alerts
|

Towards more Durable Electrochemical Capacitors by Elucidating the Ageing Mechanisms under Different Testing Procedures

Abstract: Electrical double‐layer capacitors (EDLCs) commonly denoted supercapacitors are rechargeable energy storage devices with excellent power and energy delivery metrics intermediate to conventional capacitors and batteries. High‐voltage aqueous electrolyte based EDLCs are particularly attractive due to their high‐power capability, facile production, and environmental advantages. EDLCs should last for thousands of cycles and evaluation of future cell chemistries require long‐term and costly galvanostatic cycling. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 90 publications
2
15
0
Order By: Relevance
“…He et al described the fading phenomena associated with voltage floating test extensively in his article. 68 There are similar kind deteriorates in cell performance shown in previous articles. 69,70 The stability of iron selenide electrode was examined by repeated cyclic curves for 4000 cycles recorded through constant 100 mV/s scan rate.…”
Section: Supercapacitive Performance Of Iron Selenide Electrodesupporting
confidence: 69%
“…He et al described the fading phenomena associated with voltage floating test extensively in his article. 68 There are similar kind deteriorates in cell performance shown in previous articles. 69,70 The stability of iron selenide electrode was examined by repeated cyclic curves for 4000 cycles recorded through constant 100 mV/s scan rate.…”
Section: Supercapacitive Performance Of Iron Selenide Electrodesupporting
confidence: 69%
“…The motivation for this study was the relatively high oxidation potential of the Br À specimen, which might be beneficial for the total cell voltage and capacitance but harmful for the carbon electrode during long-term operation, as it has been reported that carbon oxidation might occur even below the water decomposition voltage. [23][24]61] In fact, initial work demonstrating the application of KBr as a redox-active agent confirmed that the redox activity of Br À is observed at rather elevated capacitor voltages. [62] This might cause the carbon surface to be prone to surficial oxidation and capacitance fade.…”
Section: Introductionmentioning
confidence: 89%
“…In this paper, we report on the electrochemical performance of a carbon‐based electrochemical capacitor operating with a redox active electrolyte based on a bromide/bromate redox couple in an aqueous electrolyte. The motivation for this study was the relatively high oxidation potential of the Br − specimen, which might be beneficial for the total cell voltage and capacitance but harmful for the carbon electrode during long‐term operation, as it has been reported that carbon oxidation might occur even below the water decomposition voltage . In fact, initial work demonstrating the application of KBr as a redox‐active agent confirmed that the redox activity of Br − is observed at rather elevated capacitor voltages .…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations